What are the differences between on-ice and off-ice side-cutting maneuver? A kinematic and electromyographic comparative analysis of ice hockey players - Yu, Zijun; Bi, Gengchao; Wang, Weikai; Qin, Ying; Song, Zihan; Wu, Fengyu (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionOff-ice training is foundational for developing key physical qualities such as strength and power in ice hockey, but its biomechanical transference to on-ice performance is not well understood. This is critical, as maneuvers like side-cutting carry a high injury risk, potentially linked to environmental differences. This study aimed to compare the hip and knee kinematics and neuromuscular control strategies of elite ice hockey players during side-cutting maneuvers in on-ice versus off-ice environments, and to explore the potential injury implications associated with these biomechanical differences.MethodsTwenty elite male ice hockey players performed standardized 45° side-cutting maneuvers on and off the ice. A 12-camera motion capture system and surface electromyography (sEMG) were used to collect kinematic and muscle activation data. Biomechanical analysis was conducted using OpenSim for modeling, with one-dimensional Statistical Parametric Mapping (SPM1D) for continuous curve analysis and SPSS for discrete data points.ResultsThe on-ice maneuver demonstrated fundamentally different biomechanical patterns. Kinematically, athletes exhibited significantly greater hip flexion, hip abduction, and knee flexion on-ice. Most notably, a complete reversal in frontal plane knee motion was observed, shifting from a varus posture off-ice to a valgus posture on-ice. Neuromuscularly, a paradoxical strategy was revealed: while individual muscle activation (IEMG, RMS) was significantly lower on-ice, the muscle co-activation index (CI) of the knee and ankle joints was significantly higher.DiscussionThe findings reveal a key adaptive trade-off: the on-ice maneuver is kinematically riskier (knee valgus) but biomechanically more efficient (lower muscle work). The increased co-activation appears to be a protective neural strategy to enhance joint stability on the low-friction surface, compensating for the vulnerable posture. This underscores a critical gap in training specificity, as off-ice patterns do not replicate on-ice stability demands. Therefore, optimal training programs must integrate exercises that simulate on-ice loading characteristics to better prepare athletes and mitigate injury risk.